Bronsted-acid-mediated divergent reactions of betti bases with indoles: an approach to chromeno[2,3-b]indoles through intramolecular dehydrogenative C2-alkoxylation of indole - Deb, Mohit L.; Pegu, Choitanya Dev; Deka, Bhaskar; Dutta, Prantu; Kotmale, Amol S.; Baruah, Pranjal K. (European Journal of Organic Chemistry, 2016)
Divergent reactions of various 1-(aminoalkyl) naphthols and 2-(aminoalkyl) phenols (commonly known as Betti bases) with indoles under Bronsted acid catalysis is reported. With the reaction strategies, one can efficiently synthesize important indole derivatives such as 3-(alpha,alpha-diarylmethyl)indoles and chromeno[2,3-b]indoles. Furthermore, we disclose here a new C-C bond-cleavage reaction, in which naphthol and phenol behave as leaving groups to produce diarylmethanes. Inexpensive reagents such as p-toluenesulfonic acid monohydrate and molecular iodine are used to catalyze the reactions. No metal catalyst is required. The starting material of the reactions, Betti bases, are easily prepared from a three-component reaction of naphthol/phenol, aldehydes, and secondary amines. The mechanisms for the reactions are established through some control experiments. Quinone methide is the key intermediate for all the reactions reported herein.
Keywords: Betti bases; C-O bond formation; Dearylation; Fused-ring systems; nitrogen heterocycles